Knockdown of LncRNA-XIST Suppresses Proliferation and TGF-β1-Induced EMT in NSCLC Through the Notch-1 Pathway by Regulation of miR-137 - Wang, Xi; Zhang, Guojun; Cheng, Zhe; Dai, Lingling; Jia, Liuqun; Jing, Xiaogang; Wang, Huan; Zhang, Rui; Liu, Meng; Jiang, Tianci; Yang, Yuanjian; Yang, Meng (Genetic testing and molecular biomarkers, 2018)
Noncoding RNAs (ncRNAs), primarily microRNAs and long ncRNAs, play important roles in lung cancer. However, the role of long ncRNA (lncRNA)-X-inactive specific transcript (XIST) in non-small-cell lung cancer (NSCLC) is unclear. The purpose of this study was to explore the biologic function and potential mechanism of XIST in NSCLC progression. XIST, miR-137, and Notch-1 expression were detected by quantitative real-time PCR (qRT-PCR). Levels of proliferation- and epithelial-mesenchymal transition (EMT)-related proteins were assessed by Western blot. The correlations between XIST and miR-137, as well as miR-137 and Notch-1, were evaluated by bioinformatic analysis and luciferase reporter assays. We confirmed that XIST is aberrantly upregulated in NSCLC tissues and cell lines. XIST depletion inhibited cell proliferation and TGF-β1-induced EMT in A549 and H1299 cells. Spearman's correlation analysis showed an inverse correlation between miR-137 and XIST in NSCLC tissues, and miR-137 levels were found to be aberrantly reduced in A549 and H1299 cells. Furthermore, XIST could act as an endogenous sponge by directly binding to miR-137, negatively regulating its expression. miR-137 overexpression inhibited proliferation and TGF-β1-induced EMT in A549 and H1299 cells, whereas XIST could reverse the inhibitory effect of miR-137 on proliferation and TGF-β1-induced EMT. In addition, Notch-1 was identified as a direct target gene of miR-137, with the XIST-miR-137 axis regulating activation of the Notch-1 pathway. We identified a branch of the XIST/miR-137/Notch-1 pathway that regulates proliferation and TGF-β1-induced EMT in NSCLC, which could be involved in NSCLC progression.